Micropatterned silica thin films with nanohydroxyapatite micro-aggregates for guided tissue regeneration (2023)
Surface modification of biomaterials has been shown to improve the biological response to dental implants. The ability to create a controlled micro-texture on the implant via additive surface modification techniques with bioactive nanohydroxyapatite (nanoHA) may positively influence guided tissue regeneration. Objective: The main goal of this study was to produce micro-fabricated SiO 2 surfaces modified with nanohydroxyapatite particles and to characterize their influence on the biological response of Human Dental-Pulp Mesenchymal Stem Cells (hDP-MSCs) and Streptococcus mutans. Materials and methods: A combined methodology of sol-gel and soft-lithography was used to produce micropatterned SiO 2 thin films with different percentages of nanoHA micro-aggregates. The surfaces were characterized by SEM/EDS, FT-IR/ATR, AFM, XPS quantitative elemental percentage and contact angle measurements. Biological characterization was performed using hDP-MSCs cultures, while Streptococcus mutans was the selected microorganism to evaluate the bacterial adhesion on the thin films. Results: Micropatterned SiO 2 surfaces with 0%, 1% and 5% of nanoHA micro-aggregates were successfully produced using a combination of sol-gel and soft-lithography. These surfaces controlled the biological response, triggering alignment and oriented proliferation of hDP-MSCs and significant differences in the adhesion of S. mutans to the different surfaces. Significance: The micropatterned surfaces exhibited biocompatible behavior that induced an oriented adhesion and proliferation of hDP-MSCs while SiO 2 presented low bacterial adhesion. These results show that the combination of sol-gel with soft-lithography is a good approach to create micropatterned surfaces with bioactive nanoparticles for guided tissue regeneration. © 2012 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.